Amorphous alloy strengthened stainless steel manufactured by selective laser melting: Enhanced strength and improved corrosion resistance. (15th April 2018) - Zhang, Yuanjie; Zhang, Jinliang; Yan, Qian; Zhang, Lei; Wang, Min; Song, Bo; Shi, Yusheng
Abstract: In order to enhance the strength and wear characteristics of stainless steel, Fe-based amorphous alloy with ultra-high strength was introduced to reinforce stainless steel through selective laser melting. The intrigued finding was that the amorphous alloy strengthened stainless steel exhibited an increased tensile strength from 819 MPa to 1090 MPa, a lower coefficient of friction (from 0.62 to 0.49) and a higher corrosion resistance. The enhancements of properties are contributed to the oxygen purification of Y element and solid solution of Co and Mo elements, as well as the grain refinement strengthen with the introduction of the amorphous alloy. Graphical abstract: Unlabelled Image